2021
DOI: 10.1186/s12902-021-00864-w
|View full text |Cite
|
Sign up to set email alerts
|

NEUROD1 mutation in an Italian patient with maturity onset diabetes of the young 6: a case report

Abstract: Background Maturity Onset Diabetes of the Young (MODY) is a monogenic, autosomal, dominant disease that results in beta-cells dysfunction with consequent hyperglycaemia. It represents a rare form of diabetes (1–2% of all the cases). Sulphonylureas (SUs) represent the first-line treatment for this form of diabetes mellitus. NEUROD1 is expressed by the nervous and the pancreatic tissues, and it is necessary for the proper development of beta cells. A neurogenic dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In maturity-onset diabetes of the youth (MODY), several studies demonstrated some NEUROD1 candidate mutations, including NEUROD1 p.Pro197His, p.Asp202Glu, p.Leu157Arg, and p.Arg103Pro ( Ang et al, 2016 ; Aǧladioǧlu et al, 2016 ; Szopa et al, 2016 ; Horikawa et al, 2018 ; Demirci et al, 2021 ). Recently, another heterozygous mutation, NEUROD1 p.Met114Leu (c.340A > C), was reported in an Italian patient with MODY6 ( Brodosi et al, 2021 ). This variant is predicted to be pathogenic based on many prediction tools and was later confirmed in a French family ( Bouillet et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In maturity-onset diabetes of the youth (MODY), several studies demonstrated some NEUROD1 candidate mutations, including NEUROD1 p.Pro197His, p.Asp202Glu, p.Leu157Arg, and p.Arg103Pro ( Ang et al, 2016 ; Aǧladioǧlu et al, 2016 ; Szopa et al, 2016 ; Horikawa et al, 2018 ; Demirci et al, 2021 ). Recently, another heterozygous mutation, NEUROD1 p.Met114Leu (c.340A > C), was reported in an Italian patient with MODY6 ( Brodosi et al, 2021 ). This variant is predicted to be pathogenic based on many prediction tools and was later confirmed in a French family ( Bouillet et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Over the next 20 years, NEUROD1 variants have been reported as causative of diabetes in almost 20 families ( 22 ). More recently, several other cases of MODY6 have been diagnosed all around the world, mainly due to widespread use of NGS technology ( 23 28 ). NEUROD1 is a transcription factor that is implicated in early development and differentiation of pancreatic α- and β-cells ( 29 ) and in activation of insulin gene transcription ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Brodosi et al. described a NEUROD1 variant in a 48-year-old patient diagnosed with MODY at the age of 25 ( 28 ). Making the right genetic diagnosis of MODY6 is important to start adequate treatment as soon as possible to prevent chronic hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…NEUROD1 inactivation during the differentiation of human embryonic stem cells causes neonatal diabetes mellitus and defective β-cell function ( Romer et al, 2019 ). Early-onset diabetes due to homozygous or heterozygous NEUROD1 mutations have also been reported in human patients ( Kristinsson et al, 2001 ; Liu et al, 2007 ; Gonsorčíková et al, 2008 ; Rubio-Cabezas et al, 2010 ; Chapla et al, 2015 ; Bouillet et al, 2020 ; Brodosi et al, 2021 ), thus NEUROD1 is associated with maturity-onset diabetes of the young (MODY), i.e., MODY6 ( Horikawa and Enya, 2019 ). Heterozygous NEUROD1 mutations are also linked to autosomal dominant type 2 diabetes ( Malecki et al, 1999 , 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…The conserved bHLH domain is located at aa101–153. Mutations within the region coding bHLH, including NEUROD1 R103P , NEUROD1 E111K and NEUROD1 M114L , probably abolish the binding of the mutant proteins to the promoters of target genes ( Kristinsson et al, 2001 ; Szopa et al, 2016 ; Brodosi et al, 2021 ). These mutations are associated to MODY.…”
Section: Introductionmentioning
confidence: 99%